Statistical Capacity Building : Case Studies and Lessons Learned - Morrison, Thomas (Manuals and Guides, 2005)
IMF technical assistance provided by the Statistics Department--toward assisting IMF member countries in developing the ability to provide reliable and comparable economic and financial data on a timely basis to policymakers and markets--has increased more than fourfold over the past decade. This assistance has proven critical in countries building their statistical capacity so as to come into line with international data standards in an increasingly globalized and electronically interconnected world. Statistical Capacity Building: Case Studies and Lessons Learned presents four case studies drawn from experience in three countries in transition to the market, two of which were also in postconflict situations, in the 1990s and early 2000s: Cambodia, Bosnia and Herzegovina, and Ukraine. Issues of setting, institutional and statistical arrangements, strategies, and implementation are examined, and lessons learned.